Communities of practice: a study in a research group - Engelman, Raquel; Schreiber, Dusan; Bohnenberger, Maria Cristina; Bessi, Vânia Gisele (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
Situated Learning Theory considers that learning is socially constructed and based on concrete situations and that knowledge is primarily not abstract and symbolic but rather provisional, mediated and socially constructed, having intersubjective meanings ascribed to practices shared at the organization. The aim of this research was to understand in the light of the situated learning approach the learning process of a research group conceived of as a community of practice at a public university in Brazil’s south. Data were collected both from a three-month period non-participant observation in the laboratory where the group works and from 12 semi-structured interviews. Based on the results, it was possible to identify to different extents communities of practice elements presented by the theory in question such as environment/context, leadership, connectivity, formal/informal learning and non-human artifacts.